Body, Atmosphere, and Climatic Typology: toward an Architecture for Everyday Life - García-Germán, Javier (Cuadernos de Proyectos Arquitectónicos, 2020)
Abstract During the last two decades, in the context of a growing awareness of the environment and climate change, architecture has explored the design opportunities opened up by the fields of thermodynamics and ecology. Focusing on the quantitative and performance-oriented approaches that have prevailed in recent years, architecture has explored new design potentials. However, this new sensibility has been approached primarily from a technical point of view and has focused on quantifying the thermodynamic performance of buildings, overlooking the equally important cultural aspects of this endeavor. Apart from this quantitative and technical approach, architecture needs to have a qualitative outlook if it is to address the connections that exist between the local climate of a given place, the effect of the spatial and material particularities of architecture on interior atmospheres, and the everyday lifestyles of its users. Contrary to the parametric approaches that have dominated thermodynamic architecture during the last decade, climatic typologies are a powerful tool in bridging the gulf that exists between a given local climate and specific everyday life patterns. Climatic typologies —both historical and contemporary— very explicitly show how architecture can determine the interaction between outdoor climate and the way people live and socialize, offering the opportunity to connect the spatial and material lineaments of architecture to the specific physiological and psychological behaviors of its users, bridging the gulf between the thermodynamic processes induced by architecture and the everyday behavior of its inhabitants. This essay presents the architectural ideas that ideologically ground the approach. Starting from human psychosomatic behavior and everyday behavioral situations, the essay will explore how climatic typologies, both historical and contemporary, offer disciplinary knowledge essentially to an understanding of the connections between architecture, climate, and living patterns. Mediating between the technical and the cultural, this essay seeks to redefine the idea of typology, conflating the formal and material structure of the architectural type, with the microclimates it elicits and the behavior of its users. Superseding performative determinism, it proposes an open interaction between architecture, atmosphere, and human body.